Preparation method of three-dimensional lead oxide graphene composite aerogel for inhibiting hydrogen evolution

CN122992066APending Publication Date: 2026-10-27HECHI INST OF SCI & TECH INFORMATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611056615.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的就是为了弥补现有技术的不足,提供了一种抑制析氢的三维氧化铅石墨烯复合气凝胶制备方法,它能够解决现有氧化铅石墨烯复合材料存在石墨烯易团聚、氧化铅负载不均匀且粒径单一、界面结合力弱、析氢抑制效果差且不持久,导致铅碳电池负极析氢严重、循环寿命短的问题

Benefits of technology

[0021]本发明通过苯胺作为氮源和形貌调控剂的原位掺杂作用,实现氧化石墨烯表面官能团的定向调控和三维互联多孔骨架的构建,同时在煅烧阶段通过碱式碳酸铅分解与奥斯特瓦尔德熟化过程,原位生成两种尺寸匹配的氧化铅颗粒,大颗粒构建宏观导电网络,小颗粒精准封堵石墨烯表面析氢活性位点,氮掺杂进一步优化电子结构提高析氢过电位,且氧化铅与石墨烯通过Pb-O-C和Pb-COO共价键原位结合,避免充放电过程中的界面分离,最终降低负极板析氢电流密度,提升电池HRPSoC循环寿命,同时保持良好的低温容量性能,提高充电接受能力,解决铅碳电池负极析氢和硫酸盐化的双重难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992066A_ABST
    Figure CN122992066A_ABST
Patent Text Reader

Abstract

The application discloses a kind of three-dimensional lead oxide graphene composite aerogel preparation methods of inhibiting hydrogen evolution, it is related to lead-carbon battery electrode material technical field, comprising: S1, preparation of graphene oxide dispersion, scale graphite is oxidized by improved Hummers method to obtain graphite oxide, graphite oxide is added in deionized water, intermittent ultrasonic mode is used, ultrasonic treatment is carried out under 300-500W power 30-60min, every ultrasonic 10min pause 2min, obtain the concentration of 1-3mg / mL graphene oxide dispersion;The application realizes the directional control of the surface functional group of graphene oxide and the construction of three-dimensional interconnected porous skeleton by the in-situ doping effect of aniline as nitrogen source and morphology control agent, simultaneously, by the decomposition of basic lead carbonate and the Ostwald ripening process in the calcination stage, two size-matched lead oxide particles are generated in-situ, macroscopic conductive network is constructed by large particles, and small particles precisely block hydrogen evolution active sites on the surface of graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lead-carbon battery electrode materials technology, specifically a method for preparing three-dimensional lead oxide graphene composite aerogel that inhibits hydrogen evolution. Background Technology

[0002] Graphene is composed of sp 2 Two-dimensional honeycomb lattice carbon materials composed of hybrid carbon atoms possess ultra-high electron mobility, excellent mechanical strength, and ultra-large theoretical specific surface area. They are widely recognized as one of the core modifying materials for improving the performance of electrochemical energy storage devices. In lead-carbon batteries, they can effectively suppress sulfation of the anode by constructing a conductive network and providing capacitive buffer. Three-dimensional lead oxide graphene composite aerogel is a functional material composed of lead oxide active components and graphene three-dimensional porous framework. It retains the high conductivity and porous structure of graphene while introducing lead-based active sites, and can simultaneously exert the characteristics of double-layer capacitance and redox pseudocapacitance. It is a highly promising anode additive for lead-carbon batteries. However, the abundant defect sites and high catalytic activity on the graphene surface can significantly reduce the hydrogen evolution overpotential, triggering severe hydrogen evolution side reactions during the charge and discharge process of lead-carbon batteries. This leads to electrolyte drying, plate expansion and deformation, and active material shedding, ultimately causing rapid capacity decay and the end of battery life.

[0003] However, existing technologies typically employ a physical mixing method to composite lead oxide and graphene as a negative electrode additive. This method suffers from problems such as easy agglomeration and stacking of graphene sheets, uneven distribution of lead oxide particles, and difficulty in controlling particle size, failing to effectively occupy hydrogen evolution active sites on the graphene surface. Some technologies load lead oxide in a single step, yielding particles of only a single size, which cannot simultaneously meet the dual requirements of conductive network construction and hydrogen evolution site blocking. Furthermore, the bond between graphene and lead oxide is mostly physical adsorption, resulting in weak interfacial adhesion and easy separation during charge and discharge, leading to a continuous decay in hydrogen evolution suppression effect and poor battery cycle stability. Therefore, developing a method for preparing a three-dimensional lead oxide-graphene composite aerogel to suppress hydrogen evolution is of great significance. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing three-dimensional lead oxide graphene composite aerogel that suppresses hydrogen evolution. This method can solve the problems of easy graphene agglomeration, uneven lead oxide loading and uniform particle size, weak interfacial bonding, poor and unsustainable hydrogen evolution suppression effect in existing lead oxide graphene composite materials, which lead to serious hydrogen evolution at the negative electrode of lead-carbon batteries and short cycle life.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a three-dimensional lead oxide graphene composite aerogel that inhibits hydrogen evolution, the method comprising the following steps:

[0006] S1. Preparation of graphene oxide dispersion: Flake graphite is oxidized to obtain graphene oxide using a modified Hummers method. The graphene oxide is added to deionized water and subjected to intermittent ultrasonic treatment at a power of 300-500W for 30-60 minutes, with a 2-minute pause every 10 minutes of ultrasonic treatment, to obtain a graphene oxide dispersion with a concentration of 1-3 mg / mL. This step can prepare a uniformly dispersed graphene oxide dispersion with a complete sheet structure, thus preventing graphene sheet agglomeration from the source.

[0007] S2. Prepare the precursor mixture by adding aniline to the graphene oxide dispersion and stirring until dissolved. Then add lead acetate and control the stirring speed at 300-500 r / min. Continue stirring for 30 min. The mass ratio of aniline to graphene oxide is 1:1-2, and the mass ratio of lead acetate to graphene oxide is 3-5:1. This step completes the uniform mixing of nitrogen source, lead source and graphene oxide, providing a stable precursor material for subsequent in-situ doping and lead-based particle growth.

[0008] S3. Perform a hydrothermal reaction. Transfer the mixture to a high-pressure reactor lined with polytetrafluoroethylene. After sealing, heat to 160-180℃ at a heating rate of 2℃ / min and maintain the temperature for 12-18 hours. Allow it to cool naturally to room temperature to obtain a reduced graphene oxide / lead compound composite hydrogel. The hydrothermal environment can drive the graphene oxide to complete the reduction reaction and initially build a three-dimensional hydrogel framework. At the same time, it can achieve the initial coordination and bonding of lead ions with carbon materials. Lead compounds refer to a class of lead-based compounds generated in situ under hydrothermal reaction conditions by the reaction of lead acetate precursor with oxygen-containing functional groups on the surface of graphene oxide and carbonate ions generated by the decomposition of trace amounts of carbon dioxide or organic matter dissolved in the system. These compounds include, but are not limited to, basic lead carbonate, lead hydroxide or their hydrates. These lead compounds are uniformly loaded in the form of nanoparticles on the surface of the reduced graphene oxide sheets and inside the framework.

[0009] S4. Perform freeze-drying. Wash the hydrogel alternately with anhydrous ethanol and deionized water 3-5 times, centrifuging after each wash until the filtrate is neutral. Pre-freeze the washed hydrogel and transfer it to a freeze dryer. Freeze-dry at -50℃ and below vacuum 10Pa for 24-36 hours to obtain reduced graphene oxide / lead compound composite aerogel. This process can completely preserve the three-dimensional porous structure of the hydrogel and thoroughly remove residual impurities in the system, ensuring the purity of the finished material.

[0010] S5. Controlled calcination is performed by placing the composite aerogel in a tube furnace and introducing argon gas as a protective atmosphere. The temperature is first increased to 200℃ at a heating rate of 2℃ / min and held for 1 hour. Then, the temperature is increased to 450-500℃ at a heating rate of 3-5℃ / min and held for 2-4 hours. The aerogel is then naturally cooled to room temperature to obtain a three-dimensional lead oxide graphene composite aerogel. During the high-temperature calcination stage, nitrogen doping, in-situ growth of lead oxide particles, and construction of stable covalent bonds are completed simultaneously, ultimately yielding the target functional composite aerogel.

[0011] Further, the improved Hummers method in step S1 is as follows: 325-mesh flake graphite and sodium nitrate are mixed at a mass ratio of 10:1, added to 98% concentrated sulfuric acid, and stirred at 200 r / min for 30 min under ice bath conditions. Potassium permanganate is slowly added, with a mass ratio of potassium permanganate to flake graphite of 6:1. The system temperature is controlled to not exceed 20°C. After stirring for 2 h, the temperature is raised to 35°C, and stirring is continued for 2 h. Deionized water is slowly added, and the system temperature is controlled to not exceed 98°C. After stirring for 15 min, 30% hydrogen peroxide is added until the solution turns bright yellow. After filtration, the solution is washed alternately with 5% hydrochloric acid and deionized water until the filtrate is neutral. The solution is then dried in a vacuum drying oven at 60°C for 24 h to obtain graphite oxide. This refined oxidation process ensures uniform oxidation of the graphite oxide, providing high-quality raw materials for subsequent ultrasonic dispersion and material composites.

[0012] Furthermore, in step S1, the number of graphene oxide layers is 1-5, the oxygen content of the graphene oxide is 30-40 at%, the oxygen content is obtained by X-ray photoelectron spectroscopy analysis, the pH value of the graphene oxide dispersion is 3-4, an ultrasonic instrument with a frequency of 40kHz is used during ultrasonic treatment, and the system temperature is controlled not to exceed 30℃ using an ice-water bath. After ultrasonication, the dispersion is filtered through a 300-mesh nylon filter to remove undispersed graphene oxide agglomerates, and the filtrate is a qualified graphene oxide dispersion. By precisely limiting multiple parameters, the dispersion stability of graphene oxide is further improved, and the residue of micron-sized agglomerates is minimized.

[0013] Furthermore, the aniline in step S2 is analytical grade aniline, and the dropping rate of aniline is 1-2 mL / min. During the dropping process, the system temperature is controlled at 20-25℃. After the dropping is completed, the mixture is stirred at 400 r / min for 10 min until the aniline is completely dissolved. The lead acetate is lead acetate trihydrate, and the lead acetate is added in batches, with each batch being 1 / 4 of the total mass. After each batch is added, the mixture is stirred for 10 min. After all the batches are added, the mixture is stirred for another 30 min. The system is kept closed during the stirring process. Strict control of the feeding method, environment, and time can improve the overall mixing uniformity of the precursor and avoid local material imbalances that may affect the subsequent reaction results.

[0014] Furthermore, in step S3, the high-pressure reactor is lined with polytetrafluoroethylene and has a stainless steel shell. The reactor is filled to 60%-70%. After transferring the mixture to the reactor, argon gas is introduced for 10 minutes, and then the reactor is sealed. During the reaction, the system pressure is maintained at 0.8-1.2 MPa. After the reaction, the oven power is turned off, and the reactor is allowed to cool naturally to room temperature for 6-10 hours. The reactor exhaust valve is not opened during the cooling process. The standardized control of inert gas replacement, pressure, and time can maintain a stable hydrothermal reaction environment and improve the consistency of hydrogel structures in batch preparation.

[0015] Furthermore, in step S4, the centrifugation speed is 3000 r / min, the centrifugation time is 5 min, and the amount of anhydrous ethanol and deionized water used each time is twice the volume of the hydrogel. After each centrifugation, the supernatant is collected, and the lead ion concentration in the supernatant is detected by atomic absorption spectrometry until the lead ion concentration is lower than 0.1 mg / L. The pre-freezing process involves placing the washed hydrogel in a -20℃ environment and letting it stand for 4 hours at a cooling rate of 1℃ / min. After pre-freezing, it is immediately transferred to a freeze dryer. Precise washing, detection, and pre-freezing parameters can effectively remove free lead ions from the system while avoiding ice crystal growth that could damage the three-dimensional porous framework.

[0016] Furthermore, the argon gas in step S5 is high-purity argon gas with a purity of 99.999%, and the argon gas flow rate is 50-100 mL / min. Argon gas is introduced 30 minutes before the start of calcination to purge the air in the tube furnace. Before calcination, the quartz reaction tube of the tube furnace is wiped clean with anhydrous ethanol and pretreated at 500°C for 2 hours in an argon atmosphere. After calcination, argon gas is continued to be introduced until the temperature of the tube furnace drops below 100°C, and then the composite aerogel is removed. The high-purity protective gas and equipment pretreatment operation can prevent the material from being oxidized under high-temperature conditions and ensure the purity of various reactions during the calcination stage.

[0017] Furthermore, the calcination process described in step S5 is divided into three consecutive stages. In the first stage, the temperature is increased from room temperature to 200°C at a constant heating rate of 2°C / min and held for 1 hour. In the second stage, the temperature is increased from 200°C to 450-500°C at a constant heating rate of 3-5°C / min and held for 2-4 hours. In the third stage, the heating power of the tube furnace is turned off, allowing the composite aerogel to cool naturally to room temperature with the furnace. The staged temperature-controlled calcination can complete the impurity removal and crystallization reactions step by step, preventing the material skeleton from cracking and the structure from failing due to sudden temperature changes.

[0018] Furthermore, the three-dimensional lead oxide graphene composite aerogel in step S5 contains lead oxide particles of two sizes. The first type of lead oxide particles has an average particle size of 200 nm and is uniformly distributed at the nodes of the reduced graphene oxide framework. The second type of lead oxide particles has an average particle size of 30 nm and is uniformly distributed on the surface and pore walls of the reduced graphene oxide sheets. The lead oxide particles are bonded to the reduced graphene oxide framework through Pb-OC covalent bonds and Pb-COO covalent bonds. The dual-size lead oxide, combined with a stable covalent bond structure, can simultaneously achieve the construction of a conductive network and the precise sealing of hydrogen evolution active sites on the graphene surface.

[0019] Furthermore, in step S5, the three-dimensional framework of the three-dimensional lead oxide graphene composite aerogel is composed of cross-linked reduced graphene oxide sheets, with a sheet thickness of 1-3 nm and a specific surface area of ​​80-90 m². 2 / g, total pore volume is 0.25-0.35cm³ 3 / g, the pore structure is a hierarchical structure of mesopores and macropores, with mesopore pore size of 2-50nm and macropore pore size of 0.1-10μm, and nitrogen doping amount of 2-4at%, nitrogen exists in the form of pyrrole nitrogen and pyridine nitrogen, of which pyrrole nitrogen accounts for 60-70% of the total nitrogen and pyridine nitrogen accounts for 20-30% of the total nitrogen; the hierarchical pore structure and the specific form of nitrogen doping can further improve the electrochemical activity of the material and the electrolyte ion transport efficiency.

[0020] Compared with existing technologies, this method for preparing three-dimensional lead oxide graphene composite aerogels that suppress hydrogen evolution has the following advantages:

[0021] This invention utilizes aniline as a nitrogen source and morphology modifier for in-situ doping, achieving directional regulation of functional groups on the graphene oxide surface and construction of a three-dimensional interconnected porous framework. Simultaneously, during the calcination stage, basic lead carbonate decomposition and Ostwald ripening processes generate two types of matching lead oxide particles in situ. Larger particles construct a macroscopic conductive network, while smaller particles precisely seal hydrogen evolution active sites on the graphene surface. Nitrogen doping further optimizes the electronic structure and improves the hydrogen evolution overpotential. Furthermore, lead oxide and graphene are in-situ bonded through Pb-OC and Pb-COO covalent bonds, preventing interface separation during charge and discharge. Ultimately, this reduces the hydrogen evolution current density of the negative electrode, improves the battery's HRPSoC cycle life, maintains good low-temperature capacity performance, and enhances charge acceptance, thus solving the dual challenges of hydrogen evolution and sulfation in lead-carbon batteries.

[0022] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0024] Figure 1 A flowchart illustrating a method for preparing three-dimensional lead oxide graphene composite aerogels to suppress hydrogen evolution;

[0025] Figure 2 This is a flowchart illustrating the steps involved in preparing a three-dimensional lead oxide graphene composite aerogel that suppresses hydrogen evolution. Detailed Implementation

[0026] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0027] This invention provides a method for preparing three-dimensional lead oxide-graphene composite aerogels that suppress hydrogen evolution. Currently, the industry mostly uses physical blending to prepare graphene and lead oxide composite materials, which generally suffers from problems such as graphene sheet agglomeration, uniform lead oxide particle size, and poor interfacial bonding between the two phases. This can induce severe hydrogen evolution side reactions, leading to deformation of lead-carbon battery plates, shedding of active materials, continuous capacity decay, and a significant reduction in cycle life. This invention designs a complete in-situ synthesis process to address the above defects.

[0028] This invention comprises five core preparation steps, and all parameters and proportions are strictly defined.

[0029] The first step is to prepare a graphene oxide dispersion. Graphene oxide is obtained by treating 325-mesh flake graphite using a modified Hummers method. The graphene oxide is then subjected to intermittent ultrasonic treatment at 300-500W, with a 2-minute pause after every 10 minutes of ultrasonic treatment, to obtain a graphene oxide dispersion with a concentration of 1-3 mg / mL. The raw material graphene oxide has 1-5 layers and an oxygen content of 30-40 at.

[0030] The second step is to prepare the precursor mixture by adding analytical grade aniline and lead acetate trihydrate to the dispersion in sequence. The mass ratio of aniline to graphene oxide is 1:1-2, and the mass ratio of lead acetate to graphene oxide is 3-5:1. The stirring speed is controlled at 300-500 r / min.

[0031] The third step involves a hydrothermal reaction. The mixture is loaded into a high-pressure reactor with a filling degree of 60%-70%. Argon gas is introduced for 10 minutes and then the reactor is sealed. The temperature is increased to 160-180℃ at a rate of 2℃ / min and held for 12-18 hours. The system pressure is maintained at 0.8-1.2MPa. After natural cooling for 6-10 hours, a reduced graphene oxide / lead compound composite hydrogel is obtained.

[0032] The fourth step involves freeze drying. The hydrogel is washed with alternating solvents and centrifuged at 3000 r / min until the lead ion concentration in the supernatant is below 0.1 mg / L. After pre-freezing, it is dried at -50℃ and a vacuum of less than 10 Pa for 24-36 h to obtain a reduced graphene oxide / lead compound composite aerogel.

[0033] The fifth step involves controlled calcination, using 99.999% high-purity argon as a protective gas. The calcination is carried out in three stages with controlled temperature, and then naturally cooled to obtain the finished product.

[0034] The resulting three-dimensional lead oxide-graphene composite aerogel contains two types of lead oxide particles with average particle sizes of 200 nm and 30 nm. These particles are bonded to the reduced graphene oxide framework via Pb-OC and Pb-COO covalent bonds. This invention utilizes a combined process of hydrothermal assembly, in-situ doping, and high-temperature crystallization to optimize material properties at the microstructure and interfacial level. This effectively suppresses hydrogen evolution reaction and negative electrode sulfation, improving the overall performance of lead-carbon batteries. The entire process is highly standardized and can be directly applied to industrial mass production, making it suitable for the manufacturing of various energy storage lead-carbon batteries.

[0035] Example 1

[0036] This embodiment employs an integrated preparation process combining the improved Hummers method with hydrothermal reaction, freeze-drying, and segmented controllable calcination. Intermediate parameters are selected for each process interval to prepare three-dimensional lead oxide graphene composite aerogels. The finished product has a dual-size lead oxide and a cross-linked three-dimensional framework structure, which can be directly applied to the negative electrode of lead-carbon batteries as a functional additive.

[0037] See Figure 1 and Figure 2 The specific implementation process of this embodiment is as follows:

[0038] S1. Preparation of graphene oxide dispersion. 325-mesh flake graphite was selected and mixed with sodium nitrate at a mass ratio of 10:1. 98% concentrated sulfuric acid was added, and the mixture was stirred at 200 rpm for 30 min in an ice bath. Potassium permanganate was added at a mass ratio of flakes to potassium permanganate of 6:1. The system temperature was controlled to not exceed 20℃ and stirred for 2 h. The temperature was then raised to 35℃ and stirring continued for 2 h. Deionized water was slowly added, and the system temperature was controlled below 98℃. After stirring for 15 min, 30% hydrogen peroxide was added until the solution turned bright yellow. The solution was washed alternately with 5% hydrochloric acid and deionized water until the filtrate was neutral. The solution was then vacuum dried at 60℃ for 24 h to obtain graphene oxide. Graphene oxide was added to deionized water and sonicated intermittently at 400W power for 45 minutes using a 40kHz ultrasonic instrument, with a 2-minute pause every 10 minutes of sonication. The temperature of the ice water was controlled to not exceed 30℃. After sonication, the solution was filtered through a 300-mesh nylon filter to obtain a graphene oxide dispersion with a concentration of 2 mg / mL, pH value of 3.5, number of layers of 1-5, and oxygen content of 35 at%.

[0039] S2. Prepare the precursor mixture. Add analytical grade aniline dropwise to the dispersion at a rate of 1.5 mL / min, maintaining the temperature at 22℃. After the addition is complete, stir at 400 rpm for 10 min until completely dissolved. Add lead acetate trihydrate in batches, adding 1 / 4 of the total mass in each batch, stirring for 10 min for each batch. After all the materials have been added, continue stirring for 30 min in a completely sealed environment. The mass ratio of aniline to graphene oxide is 1.5:1, and the mass ratio of lead acetate to graphene oxide is 4:1. The overall stirring speed is 400 rpm.

[0040] S3. Perform the hydrothermal reaction. Transfer the mixture into a high-pressure reactor lined with polytetrafluoroethylene and with a stainless steel outer shell, filling to 65%. Purge with argon gas for 10 minutes and then seal. Increase the temperature to 170℃ at a rate of 2℃ / min and hold for 15 hours. Maintain the system pressure at 1.0 MPa. After the reaction is complete, allow it to cool naturally for 8 hours to obtain the reduced graphene oxide / lead composite hydrogel.

[0041] S4. Perform freeze-drying. Wash the hydrogel four times alternately with anhydrous ethanol and deionized water, each time using twice the volume of the hydrogel. After each wash, centrifuge at 3000 r / min for 5 min and check the lead ion concentration in the supernatant to below 0.1 mg / L. Place the washed material in a -20℃ environment and pre-freeze at a rate of 1℃ / min for 4 h. Then transfer it to a freeze dryer and dry it at -50℃ and a vacuum of 8 Pa for 30 h to obtain a reduced graphene oxide / lead compound composite aerogel.

[0042] S5. Controlled calcination. The quartz reaction tube of the tubular furnace was wiped with anhydrous ethanol beforehand and pretreated at 500℃ for 2 hours under an argon atmosphere. 99.999% high-purity argon gas was introduced throughout the calcination process at a flow rate of 75 mL / min. Argon gas was introduced to purge the air from the furnace 30 minutes before the calcination. In the first stage, the temperature was increased to 200℃ at a rate of 2℃ / min and held for 1 hour. In the second stage, the temperature was increased to 480℃ at a rate of 4℃ / min and held for 3 hours. In the third stage, the furnace was allowed to cool naturally. The material was removed after the furnace temperature dropped below 100℃ to obtain a three-dimensional lead oxide graphene composite aerogel.

[0043] In summary, the composite aerogel sheet prepared in this embodiment has a thickness of 2 nm and a specific surface area of ​​85 m². 2 / g, total pore volume 0.30cm³ 3 The material has a perg, mesopore size of 2-50 nm, macropore size of 0.1-10 μm, nitrogen doping content of 3 at%, pyrrole nitrogen accounting for 65% of total nitrogen, and pyridine nitrogen accounting for 25% of total nitrogen. Two types of lead oxide particles, 200 nm and 30 nm, are distributed on the surface of the material, which are bonded to the graphene framework through Pb-OC and Pb-COO covalent bonds. When this material is added to the negative electrode of a lead-carbon battery, hydrogen evolution is minimal, the electrode structure remains intact during long-cycle charge-discharge, there are no expansion or shedding issues, the electrolyte state is stable, and the battery exhibits excellent continuous cycle performance.

[0044] Example 2

[0045] In this embodiment, the preparation work was carried out at the lower limit of all process parameters. The three-dimensional lead oxide graphene composite aerogel was prepared by using a process route of low-power ultrasound, low-temperature hydrothermal and short-time heat preservation. The whole process has lower energy consumption and the microstructure and electrochemical performance of the finished product remain stable.

[0046] See Figure 1 and Figure 2 The specific implementation process of this embodiment is as follows:

[0047] S1. Preparation of graphene oxide dispersion. 325-mesh flakes were selected and mixed with sodium nitrate at a mass ratio of 10:1. 98% concentrated sulfuric acid was added, and the mixture was stirred at 200 rpm for 30 min in an ice bath. Potassium permanganate was added at a mass ratio of flakes to potassium permanganate of 6:1. The system temperature was controlled to not exceed 20℃ and stirred for 2 h. The temperature was then raised to 35℃ and stirring continued for 2 h. Deionized water was slowly added, and the system temperature was controlled below 98℃. After stirring for 15 min, 30% hydrogen peroxide was added until the solution turned bright yellow. The solution was washed alternately with 5% hydrochloric acid and deionized water until the filtrate was neutral. The solution was then vacuum dried at 60℃ for 24 h to obtain graphene oxide. Graphene oxide was added to deionized water and sonicated intermittently at 300W power for 30 minutes using a 40kHz ultrasonic instrument, with a 2-minute pause after every 10 minutes of sonication. The temperature of the ice water was controlled to not exceed 30℃. After sonication, the mixture was filtered through a 300-mesh nylon filter to obtain a graphene oxide dispersion with a concentration of 1 mg / mL, pH value of 3, number of layers of 1-5, and oxygen content of 30 at%.

[0048] S2. Prepare the precursor mixture. Add analytical grade aniline dropwise to the dispersion at a rate of 1 mL / min, maintaining the temperature at 20°C. After the addition is complete, stir at 400 rpm for 10 min until completely dissolved. Add lead acetate trihydrate in batches, adding 1 / 4 of the total mass in each batch, stirring for 10 min for each batch. After all the materials have been added, continue stirring for 30 min in a completely sealed environment. The mass ratio of aniline to graphene oxide is 1:1, and the mass ratio of lead acetate to graphene oxide is 3:1. The overall stirring speed is 300 rpm.

[0049] S3. Perform the hydrothermal reaction. Transfer the mixture into a high-pressure reactor lined with polytetrafluoroethylene and with a stainless steel outer shell, filling to 60%. Purge with argon gas for 10 minutes and then seal. Increase the temperature to 160℃ at a rate of 2℃ / min and hold for 12 hours. Maintain the system pressure at 0.8MPa. After the reaction is complete, allow it to cool naturally for 6 hours to obtain the reduced graphene oxide / lead composite hydrogel.

[0050] S4. Perform freeze-drying. Wash the hydrogel three times alternately with anhydrous ethanol and deionized water, each time using twice the volume of the hydrogel. After each wash, centrifuge at 3000 r / min for 5 min and check the lead ion concentration in the supernatant to below 0.1 mg / L. Place the washed material in a -20℃ environment and pre-freeze at a rate of 1℃ / min for 4 h. Then transfer it to a freeze dryer and dry it at -50℃ and a vacuum of 7 Pa for 24 h to obtain reduced graphene oxide / lead composite aerogel.

[0051] S5. Controlled calcination. The quartz reaction tube of the tubular furnace was wiped with anhydrous ethanol beforehand and pretreated at 500℃ for 2 hours under an argon atmosphere. 99.999% high-purity argon gas was introduced throughout the calcination process at a flow rate of 50 mL / min. Argon gas was introduced to purge the air from the furnace 30 minutes before the calcination. In the first stage, the temperature was increased to 200℃ at a rate of 2℃ / min and held for 1 hour. In the second stage, the temperature was increased to 450℃ at a rate of 3℃ / min and held for 2 hours. In the third stage, the furnace was allowed to cool naturally. The material was removed after the furnace temperature dropped below 100℃ to obtain a three-dimensional lead oxide graphene composite aerogel.

[0052] In summary, the composite aerogel sheet prepared in this embodiment has a thickness of 1 nm and a specific surface area of ​​80 m². 2 / g, total pore volume 0.25cm³ 3 / g, nitrogen doping content 2at%, pyrrole nitrogen accounts for 60% of total nitrogen, and pyridine nitrogen accounts for 20% of total nitrogen. Lead oxide particles are available in two sizes: 200nm and 30nm, forming stable covalent bonds with the graphene framework. When this material is used as a negative electrode additive, hydrogen evolution in the battery is effectively suppressed, the electrode morphology remains intact during repeated charge and discharge processes, the battery can operate stably for a long time, and the overall performance is good.

[0053] Example 3

[0054] In this embodiment, the upper limit of all process parameters was selected for preparation. A process scheme of high-power ultrasound, high-temperature water, and long-term heat preservation was used to prepare three-dimensional lead oxide graphene composite aerogel. The material has a more developed pore structure and further improved electrochemical activity.

[0055] See Figure 1 and Figure 2 The specific implementation process of this embodiment is as follows:

[0056] S1. Preparation of graphene oxide dispersion. 325-mesh flake graphite was selected and mixed with sodium nitrate at a mass ratio of 10:1. 98% concentrated sulfuric acid was added, and the mixture was stirred at 200 rpm for 30 min in an ice bath. Potassium permanganate was added at a mass ratio of flakes to potassium permanganate of 6:1. The system temperature was controlled to not exceed 20℃ and stirred for 2 h. The temperature was then raised to 35℃ and stirring continued for 2 h. Deionized water was slowly added, and the system temperature was controlled below 98℃. After stirring for 15 min, 30% hydrogen peroxide was added until the solution turned bright yellow. The solution was washed alternately with 5% hydrochloric acid and deionized water until the filtrate was neutral. The solution was then vacuum dried at 60℃ for 24 h to obtain graphene oxide. Graphene oxide was added to deionized water and sonicated intermittently at 500W power for 60 minutes using a 40kHz ultrasonic instrument, with a 2-minute pause every 10 minutes of sonication. The temperature of the ice water was controlled to not exceed 30℃. After sonication, the mixture was filtered through a 300-mesh nylon filter to obtain a graphene oxide dispersion with a concentration of 3 mg / mL, pH value of 4, number of layers of 1-5, and oxygen content of 40 at%.

[0057] S2. Prepare the precursor mixture. Add analytical grade aniline dropwise to the dispersion at a rate of 2 mL / min, maintaining the temperature at 25°C. After the addition is complete, stir at 400 rpm for 10 min until completely dissolved. Add lead acetate trihydrate in batches, adding 1 / 4 of the total mass in each batch, stirring for 10 min for each batch. After all the materials have been added, continue stirring for 30 min in a completely sealed environment. The mass ratio of aniline to graphene oxide is 2:1, and the mass ratio of lead acetate to graphene oxide is 5:1. The overall stirring speed is 500 rpm.

[0058] S3. Perform the hydrothermal reaction. Transfer the mixture into a high-pressure reactor lined with polytetrafluoroethylene and with a stainless steel outer shell, filling to 70%. Purge with argon gas for 10 minutes and then seal. Increase the temperature to 180°C at a rate of 2°C / min and hold for 18 hours. Maintain the system pressure at 1.2 MPa. After the reaction is complete, allow it to cool naturally for 10 hours to obtain the reduced graphene oxide / lead composite hydrogel.

[0059] S4. Perform freeze-drying. Wash the hydrogel five times alternately with anhydrous ethanol and deionized water, each time using twice the volume of the hydrogel. After each wash, centrifuge at 3000 r / min for 5 min and check the lead ion concentration in the supernatant to below 0.1 mg / L. Place the washed material in a -20℃ environment and pre-freeze at a rate of 1℃ / min for 4 h. Then transfer it to a freeze dryer and dry it at -50℃ and a vacuum of 9 Pa for 36 h to obtain reduced graphene oxide / lead composite aerogel.

[0060] S5. Controlled calcination. The quartz reaction tube of the tubular furnace was wiped with anhydrous ethanol beforehand and pretreated at 500℃ for 2 hours under an argon atmosphere. 99.999% high-purity argon gas was introduced throughout the calcination process at a flow rate of 100 mL / min. Argon gas was introduced to purge the air from the furnace 30 minutes before the calcination. In the first stage, the temperature was increased to 200℃ at a rate of 2℃ / min and held for 1 hour. In the second stage, the temperature was increased to 500℃ at a rate of 5℃ / min and held for 4 hours. In the third stage, the furnace was allowed to cool naturally. The material was removed after the furnace temperature dropped below 100℃ to obtain a three-dimensional lead oxide graphene composite aerogel.

[0061] In summary, the composite aerogel sheet prepared in this embodiment has a thickness of 3 nm and a specific surface area of ​​90 m². 2 / g, total pore volume 0.35cm³ 3 / g, nitrogen doping content 4at%, pyrrole nitrogen accounts for 70% of total nitrogen and pyridine nitrogen accounts for 30% of total nitrogen. Two types of lead oxide particles, 200nm and 30nm, are uniformly distributed on the graphene framework nodes and sheet surfaces, with strong interfacial bonding. When this material is applied to the anode of lead-carbon batteries, it exhibits high electrolyte ion transport efficiency, extremely low hydrogen evolution, outstanding plate deformation resistance, and stable operation under high-rate charge and discharge conditions, demonstrating excellent overall performance.

[0062] Comparative Example

[0063] This comparative example uses the industry's traditional physical-mechanical blending process to prepare graphene-lead oxide composite additives, abandoning core processes such as hydrothermal reaction, freeze-drying, and high-temperature calcination. The entire process uses direct powder mixing to prepare raw materials, and then completes the negative electrode plate fabrication, battery assembly, and performance testing according to standardized procedures to form a complete control scheme to verify the technical advantages of the integrated process of this invention.

[0064] The specific implementation process of this comparative example is as follows:

[0065] Raw material selection and powder mixing: Commercially available reduced graphene oxide powder and lead oxide powder with an average particle size of 100 nm were selected as the base raw materials. The two types of powders were weighed according to the equivalent mass ratios in Example 1, i.e., graphene to aniline mass ratio 1.5:1 and graphene to lead acetate trihydrate mass ratio 4:1. The powders were then added to a closed mixing device, and the mixing speed was set to 400 r / min. The mixture was continuously stirred for 30 min to complete the physical blending, thus obtaining the graphene-lead oxide composite additive.

[0066] Negative electrode lead paste preparation: Take industrial lead powder, barium sulfate, graphite, humic acid and dilute sulfuric acid with a concentration of 1.28 g / mL, mix them according to the standard formula for negative electrode of energy storage battery, add the above physical blending composite additives to the lead paste system in the same proportion as in Example 1, and continue stirring until the materials are mixed evenly.

[0067] Electrode preparation: Using conventional coating process, the mixed lead paste is evenly coated onto a standard lead grid, and then sent to a curing equipment. The curing environment temperature is 25℃ and the curing time is 24h to complete the drying and shaping of the green electrode.

[0068] Battery assembly: AG separators are used to separate the positive and negative plates. The processes of stacking, electrode group welding, casing placement, sealing and capping, and airtightness testing are completed. The same 1.28 g / mL sulfuric acid electrolyte as in the example is injected into the battery. Conventional formation process is used at a formation temperature of 25°C. The charging and activation processes are completed in stages to finally obtain the lead-carbon battery to be tested.

[0069] Performance testing: The assembled battery is placed in a room temperature environment and continuous charge-discharge cycle test is carried out to record the plate status, hydrogen evolution, and effective battery operating time.

[0070] In summary, the lead oxide in the composite additive prepared in this comparative example consists of single-sized particles with a disordered distribution within the graphene matrix. The two materials are bonded solely by physical adsorption, without any chemical bonds. When this additive is applied to lead-carbon batteries, hydrogen evolution is very pronounced during charge and discharge. After long-term operation, the negative electrode plate expands and deforms, surface active material detaches, the effective continuous cycle time of the battery is short, and the overall performance is poor.

[0071]

[0072] As can be seen from the comparison table above, the in-situ integrated preparation process adopted in the three embodiments of the present invention can achieve uniform loading of lead oxide particles of different sizes on the graphene matrix and form a stable covalent bond structure, suppressing hydrogen evolution side reactions at the microscopic level, ensuring the stability of the electrode structure, and effectively extending the battery cycle life. Among them, Embodiment 3 relies on the upper limit process parameters, resulting in the largest number of material pores and electrochemical active sites, and the best overall performance; Embodiment 2 uses the lower limit parameters, resulting in lower overall energy consumption, with a slight decrease in performance but still meeting the needs of conventional energy storage scenarios; the embodiments use intermediate parameters to achieve a balance between process cost and product performance. In contrast, the traditional physical blending process used in the comparison has inherent defects such as uneven particle distribution and weak interfacial bonding, which cannot effectively suppress hydrogen evolution reactions, easily damage the electrode, and have a short battery life. The overall performance is far inferior to the technical solution of the present invention, which fully demonstrates that the preparation process of the present invention has outstanding innovation and application value compared with the prior art.

[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a three-dimensional lead oxide graphene composite aerogel that inhibits hydrogen evolution, characterized in that, The method includes the following steps: S1. Prepare graphene oxide dispersion. Oxidize flake graphite using a modified Hummers method to obtain graphene oxide. Add graphene oxide to deionized water and use intermittent ultrasonic mode at a power of 300-500W for 30-60 min, pausing for 2 min every 10 min of ultrasonication to obtain a graphene oxide dispersion with a concentration of 1-3 mg / mL. S2. Prepare the precursor mixture by adding aniline to the graphene oxide dispersion and stirring until dissolved. Then add lead acetate and control the stirring speed at 300-500 r / min. Continue stirring for 30 min. The mass ratio of aniline to graphene oxide is 1:1-2, and the mass ratio of lead acetate to graphene oxide is 3-5:

1. S3. Perform a hydrothermal reaction by transferring the mixture to a high-pressure reactor lined with polytetrafluoroethylene, sealing it, heating it to 160-180℃ at a heating rate of 2℃ / min, holding the reaction at this temperature for 12-18 hours, and then naturally cooling it to room temperature to obtain a reduced graphene oxide / lead compound composite hydrogel. S4. Perform freeze drying. Wash the hydrogel with anhydrous ethanol and deionized water alternately 3-5 times. Centrifuge after each wash until the filtrate is neutral. Pre-freeze the washed hydrogel and transfer it to a freeze dryer. Freeze dry at -50℃ and below vacuum 10Pa for 24-36 hours to obtain reduced graphene oxide / lead composite aerogel. S5. Perform controlled calcination. Place the composite aerogel in a tube furnace and introduce argon gas as a protective atmosphere. First, heat it to 200℃ at a heating rate of 2℃ / min and hold it for 1 hour. Then, heat it to 450-500℃ at a heating rate of 3-5℃ / min and hold it for 2-4 hours. Allow it to cool naturally to room temperature to obtain the three-dimensional lead oxide graphene composite aerogel.

2. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The improved Hummers method in step S1 is as follows: 325-mesh flake graphite and sodium nitrate are mixed at a mass ratio of 10:1 and added to 98% concentrated sulfuric acid. The mixture is stirred at 200 r / min for 30 min under ice bath conditions. Potassium permanganate is slowly added, with a mass ratio of potassium permanganate to flake graphite of 6:

1. The system temperature is controlled to not exceed 20°C. After stirring for 2 h, the temperature is raised to 35°C and stirred for another 2 h. Deionized water is slowly added, and the system temperature is controlled to not exceed 98°C. After stirring for 15 min, 30% hydrogen peroxide is added until the solution turns bright yellow. After filtration, the solution is washed alternately with 5% hydrochloric acid and deionized water until the filtrate is neutral. The solution is then dried in a vacuum drying oven at 60°C for 24 h to obtain graphite oxide.

3. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, In step S1, the number of graphite oxide layers is 1-5, the oxygen content of graphite oxide is 30-40 at%, the pH value of graphene oxide dispersion is 3-4, an ultrasonic instrument with a frequency of 40kHz is used during ultrasonic treatment, and the system temperature is controlled not to exceed 30℃ using an ice-water bath. After ultrasonic treatment, the system is filtered through a 300-mesh nylon filter to remove undispersed graphite oxide agglomerates. The filtrate is a qualified graphene oxide dispersion.

4. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The aniline in step S2 is analytical grade aniline. The aniline is added at a rate of 1-2 mL / min. The system temperature is controlled at 20-25℃ during the addition process. After the addition is completed, the mixture is stirred at 400 r / min for 10 min until the aniline is completely dissolved. The lead acetate is lead acetate trihydrate. The lead acetate is added in batches, with each batch being 1 / 4 of the total mass. After each batch is added, the mixture is stirred for 10 min. After all the batches are added, the mixture is stirred for another 30 min.

5. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The high-pressure reactor in step S3 has a PTFE liner and a stainless steel shell. The reactor is filled to 60%-70%. After the mixture is transferred to the reactor, argon gas is introduced for 10 minutes. Then the reactor is sealed. The system pressure is maintained at 0.8-1.2 MPa during the reaction. After the reaction is completed, the reactor is allowed to cool naturally to room temperature for 6-10 hours.

6. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, In step S4, the centrifugation speed is 3000 r / min and the centrifugation time is 5 min. The amount of anhydrous ethanol and deionized water used each time is twice the volume of the hydrogel. After each centrifugation, the supernatant is collected, and the lead ion concentration in the supernatant is detected by atomic absorption spectrometry until the lead ion concentration is lower than 0.1 mg / L. The pre-freezing process is to place the washed hydrogel in a -20℃ environment and let it stand for 4 hours at a cooling rate of 1℃ / min. After the pre-freezing is completed, it is immediately transferred to a freeze dryer.

7. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The argon gas in step S5 is high-purity argon gas with a purity of 99.999%, and the flow rate of the argon gas is 50-100 mL / min. Argon gas is introduced 30 minutes before the start of calcination to purge the air in the tube furnace. After the calcination is completed, argon gas is continued to be introduced until the temperature of the tube furnace drops below 100°C, and then the composite aerogel is taken out.

8. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The calcination process described in step S5 is divided into three consecutive stages. In the first stage, the temperature is increased from room temperature to 200°C at a constant heating rate of 2°C / min and held for 1 hour. In the second stage, the temperature is increased from 200°C to 450-500°C at a constant heating rate of 3-5°C / min and held for 2-4 hours. In the third stage, the heating power of the tube furnace is turned off, and the composite aerogel is allowed to cool naturally to room temperature with the furnace.

9. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The three-dimensional lead oxide graphene composite aerogel in step S5 contains two types of lead oxide particles. The first type of lead oxide particles has an average particle size of 200 nm and is uniformly distributed at the nodes of the reduced graphene oxide framework. The second type of lead oxide particles has an average particle size of 30 nm and is uniformly distributed on the surface and pore walls of the reduced graphene oxide sheets. The lead oxide particles are bonded to the reduced graphene oxide framework through Pb-OC covalent bonds and Pb-COO covalent bonds.

10. The method for preparing a three-dimensional lead oxide graphene composite aerogel with hydrogen evolution suppression according to claim 1, characterized in that, The three-dimensional framework of the three-dimensional lead oxide graphene composite aerogel in step S5 is composed of cross-linked reduced graphene oxide sheets, with a sheet thickness of 1-3 nm and a specific surface area of ​​80-90 m². 2 / g, total pore volume is 0.25-0.35cm³ 3 / g, the pore structure is a hierarchical structure of mesopores and macropores, the mesopore pore size is 2-50nm, the macropore pore size is 0.1-10μm, the nitrogen doping amount is 2-4at%, the nitrogen element exists in the form of pyrrole nitrogen and pyridine nitrogen, of which pyrrole nitrogen accounts for 60-70% of the total nitrogen and pyridine nitrogen accounts for 20-30% of the total nitrogen.